The Effectiveness of the Policy to Waive Tax Penalties on the Compliance Rates of Motor Vehicle Taxpayers at the Samsat Regional Technical Implementation Unit in Serang Regency - Aby Fahri; H. E. Rakhmat Jazuli; Ahmad Rayhan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Motor Vehicle Tax is one of the sources of local revenue that every motor vehicle owner is required to pay, as stipulated in Banten Province Regional Regulation No. 1 of 2024 concerning Local Taxes and Local Levies. The compliance rate of motor vehicle taxpayers at the Serang Regency Samsat Technical Implementation Unit (UPTD) remains relatively low at approximately 58 percent of all registered vehicles and is accompanied by high levels of tax arrears. Consequently, the local government has implemented a policy to waive Motor Vehicle Tax penalties as an effort to increase tax payments and local revenue. This study analyzes the effectiveness of the policy to waive motor vehicle tax penalties on the compliance rate of motor vehicle taxpayers at the UPTD Samsat in Serang Regency, as well as the obstacles in its implementation. The analysis employs the theory of legal effectiveness and the theory of government action. The research method used is an empirical-juridical approach with a descriptive-analytical framework, utilizing primary data collected through interviews and secondary data sourced from legislation and legal literature. The research results indicate that local government actions including the elimination of administrative sanctions in the form of fines, the simplification of service procedures, and the optimization of tax payment services have proven effective in increasing Motor Vehicle Tax payments and local revenue realization in the short term, as reflected in revenue achievements for the 2020-2024 period, which largely exceeded targets. The decline in revenue realization in 2025 indicates that the effectiveness of these policies has not yet been fully accompanied by the establishment of sustainable taxpayer compliance and remains influenced by policy incentives. Policy implementation still faces obstacles in the form of limited service capacity, technical disruptions to facilities and infrastructure, low public awareness influenced by a legal culture of delaying tax obligations, and perceptions of unfairness among taxpayers who have historically been compliant. This study recommends strengthening policies to encourage sustainable taxpayer compliance and improving the quality of tax service delivery.